Head and neck tumor cells exhibit altered proliferation upon overexpression of nm23 genes - Herak Bosnar, Maja (Array, 2008)
Summary: nm23 was identified as a metastasis suppressor gene but is also appointed to a number of other biological functions. The goal of this study was to reveal the influence of ectopic expression of nm23-H1 and nm23-H2 on proliferation properties of head and neck tumor cells. The proliferation rate of transfected cells was evaluated using EGFP reporter system and flow cytometry. HEp-2 and CAL 33 cells transiently transfected with nm23 cDNA containing constructs exhibited enhanced proliferation. CAL 27 cells constitutively expressing GFP-Nm23-H2 protein, exhibited intense proliferation the first day after seeding, while the GFP-Nm23-H1 expressing clone started to proliferate after one-day lag period. The results on transiently transfected HEp-2 and CAL 33 cells generally confirmed previous findings connecting nm23 expression with altered proliferation of head and neck tumors. We speculate that the effects observed on stably transfected CAL 27 clones are due to their different attachment properties